Political gatekeeping and digital innovation in sustainable public procurement - Nicole Darnall; Ankita Singh; Justin M. Stritch; Shirley-Ann Augustin-Behravesh (Frontiers in Sustainability, 2026)
Governments are expanding sustainable public procurement to advance climate and social objectives. Integrating sustainability criteria alongside traditional purchasing requirements, however, increases decision complexity and creates persistent implementation barriers. Although digital tools can help manage this complexity, their adoption remains limited. This study draws on interviews with procurement technology developers and state and local officials in Europe and the United States to examine both the supply and demand sides of technology adoption for sustainable procurement. The findings identify four interrelated factors shaping uptake: political support, organizational capacity, internal processes, and technology framing. While prior research conceptualizes these factors as analytically distinct and co-equal drivers of adoption, the results suggest a hierarchical interpretation in which political support appears to play an important gatekeeping role. Across both leading and emergent governments, adoption remains limited despite substantial variation in resources, organizational structures, and technology framing. This finding provides empirical leverage and challenges the assumption that adoption drivers operate as parallel, co-equal factors. Political support appears to facilitate access to resources, legitimize process change, and reduce perceived risk, thereby shaping the extent to which organizational and technological factors contribute to adoption. The study advances a more politically grounded theory of technology adoption and develops five propositions that redirect research toward the institutional and political preconditions required to scale digital innovation in sustainable public procurement.